Job satisfaction of family physicians in European countries with different strengths of care coordination - ÇİFÇİLİ, SALİHA SERAP; CÖBEK ÜNALAN, GÜLRU PEMRA (My University, 2022)
Background. Job satisfaction of family physicians (FPs) is vitally important not only for the well-being of physicians but also for the quality of health services. Coordination of care is one of the core dimensions of strong primary care. However, studies focused on the association between care coordination and the job satisfaction of FPs is scarce. Objectives. To explore whether the factors influencing the job satisfaction of FPs differ in countries with different strengths of coordination. Material and methods. Across-sectional study was conducted among FPs in ten European countries which were divided into three groups in terms of care coordination. An online questionnaire was disseminated by e-mail to groups of FPs. Socio-demographic, working conditions and workload features were included as independent variables. Job satisfaction as the outcome variable was measured with one question. The Chi-square test was used for comparative analysis. Results. 278 FPs (72% of the targeted sample size) participated. The job satisfaction of FPs in strong and medium-level care coordination groups was higher than their counterparts in the weak-level care coordination group (p < 0.001). No association was found between the socio-demographics and workload features with job satisfaction. Only the non-existence of a gate-keeping system was associated with the increased job satisfaction of FPs in the medium-level care coordination group (p = 0.01). Conclusions. Primary health care is responsible for the coordination of care within the gigantic healthcare system, and FPs play a role in guiding patients. Studying the association between care coordination and the job satisfaction of FPs might help to build better healthcare systems. The gate-keeping system deserves special attention in this research area.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine